A confluência dos saberes formativos e os saberes práticos profissionais na docência em enfermagem - Lourenço, Abner Eliezer (2025)
This thesis investigates the formative processes that contribute to the constitution of Nursing faculty in Higher Education, understood as subjects in continuous construction and shaped by multiple experiences. The research is guided by the central question: what theoretical and methodological movements in training and teaching contribute to the constitution of the Nursing teacher? To address this question, a qualitative approach was adopted, based on the Narrative Inquiry method, which values human experience and the meanings constructed throughout professional trajectories. The study was conducted with four Nursing professors from two Higher Education Institutions located in Cuiabá, Brazil, each with a minimum of two years of teaching experience. Data were collected through questionnaires and semi-structured interviews, and analyzed using Discursive Textual Analysis (DTA). The findings reveal that teacher constitution is catalyzed by the articulation between initial training, continuing education, and pedagogical practice, and is enhanced by early teaching experiences, involvement in research projects, and critical reflection on practice. Teaching knowledge emerges as a structuring axis of this process, articulating scientific, pedagogical, and experiential dimensions, constructed in the tension between professional knowledge and educational knowledge. The research reaffirms university teaching as a legitimate field of knowledge and action and highlights the need for institutional policies that value the formative trajectories and pedagogical development of Nursing faculty, aiming for an ethical, critical, and socially engaged education.